Microstructural Investigations of Novel High Temperature Alloys Based on NiAl-(Cr,Mo) - Camelia Gombola; Alexander Kauffmann; Golnar Geramifard; Malte Blankenburg; Martin Heilmaier (Metals, 2020)
Apart from the reported transition from the fibrous morphology in NiAl-34Cr to lamellae by adding 0.6 at.% Mo, further morphology transformations along the eutectic trough in the NiAl-(Cr,Mo) alloys were observed. Compositions with at least 10.3 at.% Cr have lamellar morphology while the first tendency to fiber formation was found at 9.6 at.% Cr. There is a compositional range, where both lamellae and fibers are present in the microstructure and a further decrease in Cr to 1.8at.% Cr results in fully fibrous morphology. Alongside these morphology changes of the (Cr,Mo)ss reinforcing phase, its volume fraction was found to be from 41 to 11 vol.% confirming the trend predicted by the CALPHAD approach. For mixed morphologies in-situ X-ray diffraction experiments performed between room and liquidus temperature accompanied by EDX measurements reveal the formation of a gradient in composition for the solid solution. A new Mo-rich NiAl-9.6Cr-10.3Mo alloy clearly shows this effect in the as-cast state. Moreover, crystallographic orientation examination yields two different types of colonies in this composition. In the first colony type, the orientation relationship between NiAl matrix and (Cr,Mo)ss reinforcing phase was <semantics> ( 100 ) </semantics> NiAl|| <semantics> ( 100 ) </semantics> Cr,Mo and <semantics> 〈 100 〉 </semantics> NiAl|| <semantics> 〈 100 〉 </semantics> Cr,Mo. An orientation relationship described by a rotation of almost 60° about <semantics> 〈 111 〉 </semantics> was found in the second colony type. In both cases, no distinct crystallographic plane as phase boundary was observed.